2016
DOI: 10.1001/jamaophthalmol.2016.1275
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Utility of Self-report of Refractive Error

Abstract: Question: Are self-reported age and/or reason for first wearing optical correction accurate in identifying refractive status? Findings: In this UK adult population, both self-report of the reason for and age of first wearing glasses were found to have good accuracy for identification of myopia compared to spherical equivalent (autorefraction), in the more extreme eye. The accuracy improved if the information was combined. Overall, the prediction of hypermetropia was poor.Meaning: Questions relating to age and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Finally, a limitation in this study worth mentioning is relying on subjects’ self-reports rather than specialist eye examinations. While professional ophthalmic evaluations would be ideal to obtain detailed information on refractive error, prior studies have suggested that subjects’ self-assessment of vision status does not differ systemically from professional ophthalmic evaluations [ 29 ]. Additionally, another reason for adopting self-reported measures is to allow for rapid and large-scale survey rollout [ 30 ], which would not have been feasible given the logistical and social-distancing requirements due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a limitation in this study worth mentioning is relying on subjects’ self-reports rather than specialist eye examinations. While professional ophthalmic evaluations would be ideal to obtain detailed information on refractive error, prior studies have suggested that subjects’ self-assessment of vision status does not differ systemically from professional ophthalmic evaluations [ 29 ]. Additionally, another reason for adopting self-reported measures is to allow for rapid and large-scale survey rollout [ 30 ], which would not have been feasible given the logistical and social-distancing requirements due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The refractive error of an individual was calculated as the spherical equivalent (sphere power + 0.5 × cylinder power) averaged between the two eyes. 23 Sanfilippo et al 24 reported that lack of cycloplegia has minimal impact on population estimates of refractive error in individuals older than 20 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…Self-classification of myopia has been found to be reasonably reliable and provides lower-bound to any potential underestimation. 49 The possibility that some children may have had uncorrected refractive error may have led to an underestimation of the number of myopes. As a validation, the proportion of myopes in this study attending primary (< 13-years) and secondary school (13-18-years) was 15 and 26 per cent, respectively; comparable to the prevalence of myopia in schoolchildren reported in the recent Ireland Eye Study (12-13-years, 19.9 per cent) and to the UK NICER study (12-13-years, 16.4 per cent, 18-20-years, 18.6 per cent), so any underestimation is likely minimal.…”
Section: Limitations Of the Studymentioning
confidence: 99%